Potential of Mychorrizal Biological Fertilizer and Green Beens Intercroping in Increasing The Yield and Anthocyanin of Glutinous Corn - Pratiwi, Novilian; Fauzi, Taufik; Sudharmawan, A. A. Ketut (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Purple corn is one of the varieties that are widely developed in Thailand and America. Purple corn has a high anthocyanin content so it has potential as an antioxidant. The disadvantage of anthocyanins is that they have low stability depending on sunlight and nitrogen. Data analysis methods are carried out descriptively with literature studies, namely; 1) choose articles that are relevant and in accordance with the theme of writing; 2) conduct qualitative analysis; 3) compile articles. Based on the results of previous studies, it can be seen that the protein content of corn superimposed with orok-orok plants continues to increase and the highest content is in the treatment of 2-row planting patterns, which is 14.42%. The application of mycorrhizal fertilizer as much as 5 g can increase the protein content of sorghum which is 10.75% compared to control (without mycorrhiza) which is 9.10%. Intercropping and mycorrhiza can be the right solution to increase anthocyanin content because they are able to fix N and help absorb N into plants properly and do not cause adverse effects on the environment.